Improving canteen's service and operations management: A case study using modelling and simulation approach - Lee, Khai Loon; Puteri Nurhazira, Romzi (Penerbit UTHM, 2021)
Operating a canteen business in an audio and visual innovation centre is a small business. However, it required good operating practices to be efficient and successful. Having good operating procedures required everyone to know its goals, objectives and be familiar with its policies. Most canteen businesses in a company or organization experienced heavy flow traffic at specific times of the day, such as breakfast, lunch, and dinner times. Queuing times for workers are extremely long and cause dissatisfaction. In a canteen, there will be a possibility for numerous inefficiencies caused by various factors. Poor business process, the lack of resources, inappropriate utilization of the available resources and an inefficient layout are the possible factors that may contribute to the inefficiencies.